MECHANISM FOR DEVELOPING SCIENTIFIC CONCEPTS - Barbosa de Oliveira Baptista, Ana Eliza [UNESP]; Ferrareto Lourenco Rodrigues, Rosana; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2019)
One of the mechanisms for managing complex ideas is by blending [1] two types of knowledge: Knowledge from the domain that is the object of comprehension, and knowledge from another distinct domain that one uses to construe this comprehension. This is at the heart of the metaphorical process: to comprehend a more complex/abstract idea in terms of a more structured/concrete idea [2]. When we view a relatively complex idea in a new way, we create a narrative pattern, reducing the complexity of the idea by compression [3]. This is particularly important for science communication. In this study, we resort to the cognitive operation of blending [1] to work out a mechanism for modelling the narrative patterns underlying the effective elaboration and communication of scientific concepts. Specifically, we use the following conceptual constructs: image-schema [4], conceptual metaphor [2] and frame [5], laboured together under conceptual blending. These constructs are among the most productive ways of combining and extending abstract concepts, which are important cognitive operations for anchoring the development of scientific concepts. To illustrate our analysis we select a set of scientific concepts that express distinct types of process from two areas of knowledge: Biology and Human Sciences. We analyze how these concepts were developed by bridging the gap between the communication process evoked by linguistic material (through the interpretation of the text genre) and the research process invoked in the reader's mind that anchored the linguistic development. Throughout this analysis we show a mechanism for developing scientific concepts, which not only facilitates the communication process but also triggers the creative process, completing the research cycle.
Keywords: Scientific concepts; communication process; research process; frame narratives; blending; metaphor